Cutaneous cryptococcosis resembling keratoacanthoma - Alex Panizza Jalkh; Naira Sulany Oliveira de Sousa; Juan Diego Ribeiro de Almeida; Flávia da Silva Fernandes; Kátia Santana Cruz; Hagen Frickmann; Marcus Vinícius Guimarães Lacerda; João Vicente Braga de Souza (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Cutaneous cryptococcosis is a manifestation of systemic cryptococcal infection, characterized by polymorphic skin lesions that can make diagnosis challenging. We report an HIV-positive patient with a solitary facial nodule, initially diagnosed as keratoacanthoma. Histopathology, fungal culture, and cerebrospinal fluid analysis confirmed disseminated cryptococcosis with central nervous system involvement caused by Cryptococcus neoformans genotype VNI. He was treated with amphotericin B followed by fluconazole, resulting in complete clinical resolution. This case underscores the need to consider disseminated cryptococcosis in the differential diagnosis of tumorlike skin lesions, particularly in HIV-positive patients.